Interdisciplinary trend in the development of modern social physics - Kisel, Nanallia K. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The article analyzes one of the most original directions of modern social philosophy – social physics. The author traces its formation and evolution in the context of interdisciplinary methodology. The phenomenon of interdisciplinarity in relation to social physics provides middle-level theories and implemented in the form of private theoretical schemas from different areas of modern physical knowledge, which gives new features to the process of mathematization of socio-humanitarian knowledge. The formation of original versions of contemporary social physics, exhibiting some correlation with the phenomenon of technoscience, contributes to the explication of the epistemic space postacademisch scientific discourse. At the same time, the criteria for choosing conceptual models of physics, mathematics and other areas of knowledge for solving research problems, the limits of ontological and methodological reductionism, require further research, as well as the correlation between social physics and other research areas in modern social philosophy.
Keywords: social philosophy; social epistemology; social physics; interdisciplinarity; transdisciplinarity; actor-network theory; reductionism; mathematization of socio-humanitarian knowledge; big data